Determination of Radon Concentration and Annual Effective Dose in Dadin Kowa Dam of Yamaltu-Deba Local Government Area Gombe, Gombe State - S. Shittu; H. Seydou; S. Bullus; I. Justice (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The level of Rn-222 concentration for water samples collected from twenty (20) different locations within Dadin Kowa town, Yamaltu Deba Local Government Area (L.G.A) of Gombe State, was estimated. Liquid Scintillation Counter (Model: Tri CarbLSA1000) was used in the analysis. Dam and tap water are the two sources of water utilized. Also, an attempt was made to estimate the Excess Life Cancer Risk and Annual Effective Dose due to Ingestion for different age groups. The mean values of Radon-222 concentrations were found to be 79.90 and 63.41 ????????/???? for untreated water samples collected from dam and treated water samples collected from various taps respectively. The mean values of the corresponding Annual Effective Doses as a result of ingestion of Radon-222 in untreated sample (water) for Adult, Children and Infants were 0.58, 0.87 and 1.02????????????/????r respectively. However, for Radon-222 in treated sample (water) for Adults, Children and Infants were 0.49, 0.74 and 0.86 ????????????/????r respectively. The mean value for Excess Life Cancer Risk (ELCR) for untreated water sample (dam) were found to be for Adults 2.03×10-3, Children 3.89×10-3 and Infants 1.33×10-4 while for Excess Life Caner Risk (ELCR) for treated water sample (tap) for Adults 1.74×10-3, Children 3.43×10-3 and Infants 4.95×10-4. It can be seen from the result obtained that the mean values were above the World Health Organization 2004 average value of 1.45×10-3. In the present study, the results of radon concentrations as well as the mean values obtained for the two (2) water samples were below the Maximum Contamination Limit (MCL) of 100 ????????/???? as approved by the World Health Organization and that of MCL of 11.1 ????????/???? as also approved by United States Environmental Protection Agency (USEPA, 1991).